Readiness Of New Graduates Of Nursing To Work In Health Care Facilities In The Emergency Period Of Covid 19 Pandemic - Tamsuri, Anas (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The Corona Virus Disease -19 pandemic over the world has raised public concern and fear. The high rate of transmission and the risk of death causes threats world. Many health workers (nurses) have become victims and died from contracting this disease. The purpose of this study was to identify factors related to the level of readiness of new graduates to work in the Covid 19 Pandemic Situation. The research method was cross sectional. Sample was 110 new graduates of 3 years diploma level nurses from 20 universities in East Java. Data analysis was performed using Pearson's correlation test with a = 0.05. The results showed that achievement, physical condition, interest and mental readiness were related to the readiness of graduates to work in health services. Based on the research results, it is suggested to universities to strengthen the quality of learning experiences to strengthen the readiness of graduates.